RESPON PETANI TERHADAP INOVASI PEMANFAATAN SEKAM PADI SEBAGAI BIOE ALTERNATIF PADA KELOMPOK TANI SIDO MAKMUR DI DESA AMBOPI KABUPATEN KONAWE - Ade Sunaddi; Rosmawaty Rosmawaty; Mardin Mardin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
The utilization of rice husk waste as an alternative bioenergy source is an innovative approach that has the potential to support environmentally friendly energy production while increasing the added value of agricultural waste. However, farmers' acceptance of this innovation is largely influenced by their perceptions of its characteristics. This study aimed to analyze farmers' responses to the innovation of utilizing rice husk as an alternative bioenergy source among members of the Sido Makmur Farmer Group in Ambopi Village, Tongauna Utara District, Konawe Regency. The study employed a descriptive qualitative approach supported by simple quantitative data. All 17 members of the Sido Makmur Farmer Group were selected as informants using a census technique. Data were collected through observation, structured interviews, and documentation. Data were analyzed using the interactive model developed by Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. Farmers' responses were examined based on Rogers' five perceived characteristics of innovation, namely relative advantage, compatibility, complexity, trialability, and observability. The findings revealed that farmers showed positive responses toward the innovation of utilizing rice husk as an alternative bioenergy source. The innovation was perceived to reduce dependence on conventional energy sources, enhance the utilization of rice husk waste that had previously been considered to have little economic value, and provide a more environmentally friendly alternative energy source. In terms of compatibility, the innovation was considered appropriate for the local economic, socio-cultural, and environmental conditions because it utilizes abundant locally available raw materials. The perceived complexity of the innovation was relatively low since the required tools and materials were readily available and the production process was simple, although farmers' age and heavy daily workloads remained constraints for some respondents. Furthermore, the innovation could be easily tested on a small scale, and its benefits were readily observable, thereby strengthening farmers' confidence in accepting the innovation. The study concludes that the perceived characteristics of innovation, including relative advantage, compatibility with farmers' needs, ease of understanding, trialability, and observability, are the primary factors that foster positive farmer responses toward the utilization of rice husk as an alternative bioenergy source and have the potential to accelerate the adoption of this innovation in rural communities.